Ein Imperium wird vermessen Kartographie, Kulturtransfer und Raumerschließung im Zarenreich (1797-1919) - Jeske, Martin (De Gruyter, 2023)
This book is about the cartography and measuring of the Tsarist Russia in the nineteenth and early twentieth centuries. It views the topographical and cartographical surveying of the largest country on earth as one aspect of Russia's territorialization and examines the significance of cultural transfers from Western Europe. The maps interpreted here reveal the fragmentary self-images of this enormous empire that were created in the process.